World War II and after – responses of three british dramatists – Samuel Beckett, Harold Pinter and John Osborne - Ghazi, Afnan (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2014.